The SIMON and SPECK lightweight block ciphers - Beaulieu, Ray; Treatman-Clark, Stefan; Shors, Douglas; Weeks, Bryan; Smith, Jason; Wingers, Louis (Proceedings - ACM IEEE Design Automation Conference, 2015)
The Simon and Speck families of block ciphers were designed specifically to offer security on constrained devices, where simplicity of design is crucial. However, the intended use cases are diverse and demand flexibility in implementation. Simplicity, security, and flexibility are ever-present yet conflicting goals in cryptographic design. This paper outlines how these goals were balanced in the design of Simon and Speck.